Evaluating the Benefits and Implementation Challenges of Digital Health Interventions for Improving Self-Efficacy and Patient Activation in Cancer Survivors: Single-Case Experimental Prospective Study - Umut Arioz; Urška Smrke; Valentino Šafran; Simon Lin; Jama Nateqi; Dina Bema; Inese Polaka; Krista Arcimovica; Anna Marija Lescinska; Gaetano Manzo; Yvan Pannatier; Shaila Calvo-Almeida; et al. (Applied Sciences)
Cancer survivors face numerous challenges, and digital health interventions can empower them by enhancing self-efficacy and patient activation. This prospective study aimed to assess the impact of a mHealth app on self-efficacy and patient activation in 166 breast and colorectal cancer survivors. Participants received a smart bracelet and used the app to access personalized care plans. Data were collected at baseline and follow-ups, including patient-reported outcomes and clinician feedback. The study demonstrated positive impacts on self-efficacy and patient activation. The overall trial retention rate was 75.3%. Participants reported high levels of activation (PAM levels 1–3: P = 1.0; level 4: P = 0.65) and expressed a willingness to stay informed about their disease (CASE-Cancer factor 1: P = 0.98; factor 2: P = 0.66; factor 3: P = 0.25). Usability of the app improved, with an increase in participants rating the system as having excellent usability (from 14.82% to 22.22%). Additional qualitative analysis revealed positive experiences from both patients and clinicians. This paper contributes significantly to cancer survivorship care by providing personalized care plans tailored to individual needs. The PERSIST platform shows promise in improving patient outcomes and enhancing self-management abilities in cancer survivors. Further research with larger and more diverse populations is needed to establish its effectiveness.